Control of plant diseases : (Blackwell Scientific Publications, 1988)
The changes in British agriculture over the last half century have nowhere been more dramatic than in plant disease control. Two technologies have advanced with great rapidity and much success, namely plant breeding for disease resistance and control by fungicides. Written for practising plant pathologists and arable farmers, this volume analyzes the costs and benefits of strategies of disease control, proceeding through a series of case studies of European and North American crops.